A study of alpha particle widths in light nuclei using elastic alpha particle scattering - Hesmondhalgh, S; Beatrice, Serena (1985)
Elastic alpha particle scattering has been used to examine two different aspects of the nuclear wavefunction: to determine alpha cluster strengths in 19F and to investigate the isospin mixing amplitudes in the wavefunctions of T = 3/2 states in 19F and the first 0+; T = 2 state in 40Ca. Yield curves of gamma rays and elastically scattered alpha particles from fourteen resonances in the 15N(α,γ) 19F and 15N(α, α0) 15N reactions have been simultaneously determined. The bombarding energies range from 4.465 to 8.105 MeV and the excitation energies from 7.538 to 10.411 MeV. The alpha decay widths and total widths of the compound nuclear states populated in these resonant reactions were determined using an R-matrix analysis. Five of the states in 19F have been identified as members of alpha or triton cluster bands and the widths of these states are compared with cluster model calculations. A technique has been developed to measure small alpha widths in regions of high level density. The gamma rays from a resonance are used to define the energy region to be searched, since weak alpha particle resonances are not immediately apparent, and the beam energy is then automatically modulated to scan repeatedly the energy region of interest. High resolution was required to separate neighbouring resonances when the level density was high and this was acheived by using a differentially cryopumped windowless gas target. Three of the resonances studied in the (α + 15N) reaction were isospin forbidden. The alpha decay width of the first 5/2; T = 3/2 state in 19F has been measured and the result is in agreement with the width predicted by Wormald et al [WOR69] from a radiative alpha capture study. The 9.926 MeV state has been proposed as a candidate for the first 9/2 ; T = 3/2 and the value for the alpha width obtained from these elastic scattering experiments supports this assignment. The first 0 + ;T = 2 state in 40Ca was also studied as an isopsin forbidden resonance in the 36 Ar(α,α0 )36Ar reaction. The alpha decay width and the total width of this state has been determined. The systematics of T = 2 states in A = 4N nuclei is discussed in connection with this measurement since data are now available on all such nuclei up to mass 44.